PENGUSAHA PEREMPUAN, DIGITAL EKONOMI, KELESTARIAN LINGKUNGAN, KEBERLANJUTAN UMKM DI KOTA MALANG - Dwi Ekasari Harmadji; Sukma Perdana (Bajang Institute, 2024)
This study aims to understand the meaning of the role of women, digital economy, environmental sustainability, sustainability of MSMEs in Malang City. This study is a qualitative study, data was obtained by conducting in-depth interviews and Forum Group Discussions (FGD). The main informant is Mrs. Peni Budi Astuti as the founder of the Super Preman Organization in Malang City. The results of the study prove that the role of social organizations such as Super Preman which is dominated by female entrepreneurs in the sustainability of MSMEs in Malang City is very important. Female entrepreneurs are also skilled at using digital economy for the sustainability of their MSMEs. Environmental sustainability is also applied to the sustainability of MSMEs in Malang City. The results of the study are useful for the success of the mentoring program for empowering female MSME entrepreneurs which is being promoted by the government, especially the Ministry of Cooperatives and MSMEs